Landslides and other geomorphologic and hydrologic effects induced by earthquakes in Portugal - Vaz, Teresa (2016)
A geodatabase of landslides and other geomorphologic and hydrologic phenomena, triggered by earthquakes in Portugal, was built based on the analysis of historical records. As a result, 28 earthquake-triggered landslides were identified; the landslides were associated with 10 earthquakes that occurred between 382 and 1969. However, the landslide recognition and the definition of its precise location were difficult due to the time elapsed since the occurrence of most of the landslides and to the changes in the morphologic features of the affected slopes. Despite these limitations, it was possible to establish that most landslides were disrupted landslides that affected jointed rocks. The earthquake-triggered landslides are concentrated in the southern and central areas of Portugal, close to the main seismic sources, as opposed to the recurrent landslides induced by precipitation in the northern and central parts of the country. Other identified geomorphologic and hydrologic phenomena induced by earthquakes in mainland Portugal include: ground cracks (48 cases), liquefaction (75 cases) and water spring and fountains anomalies (262 cases). These secondary earthquake effects were reported for 5 earthquakes, but these may be considered representative only in two cases: the earthquakes of 1 November 1755 and of 23 April 1909. The distance between the site of the above-mentioned phenomena and the corresponding earthquake epicentre varies according to the earthquake magnitude and the type of phenomena. The 1755 earthquake (Mw 8.7) induced geomorphologic and hydrologic effects farther from the epicentre (maximum distance of 658 km) than the 1909 earthquake (Mw 6), whereas the effects associated with the latter were felt much closer to the earthquake epicentre (maximum distance of 172 km). The hydrologic effects brought about by the 1755 earthquake probably occurred throughout the country (distance of at least 658 km from epicentre) in contrast to ground cracks (526 km) and liquefaction (504 km).